Sniezynka : nowa sztuka z Rosji. - Morawinska, Agnieszka; National Centre for Contemporary Arts, Moskou (Moskou : Galeria Zacheta, 2002)
Khlobystin, Andrei ; Chernisheva, Olga ; Denisov, Sergey ; Shuvalov, Kiryll ; Florensky, Olga ; Florensky, Aleksandr ; Gorlova, Lyudmila ; Hengsler, Tatyana ; Yemifov, Vladislav ; Chernishov, Aristarkh ; et al.
snowgirl, National Centre for Contemporary Arts, Moskou, 19 March - 5 May 2002
kunstcatalogus
Keywords: Rusland